NAME FORMATION ISSUES IN TOPONYMY OF JONDOR DISTRICT - Narzilloyeva Manzura Shukhrat kizi (Web of Journals Publishing, 2025)
This article is devoted to the issue of the formation of toponyms located in the territory of the Jondor district of the Bukhara region. In order to clarify the content of the topic, information is provided on the method of creating new names in the formation of toponyms, the existence of a method of borrowing names from other languages, their formation in morphological and syntactic ways, the combination of composite toponym components by adaptation, fusion, control, etc.
Keywords: Bukhara, Jondor, toponym, microtoponym, N. Okhunov, N. Mingboyev, Z. Dosimov.